Review of the monograph: “Extremism in the modern world” - N. M. Mezhevich (Управленческое консультирование)
The review of the unique monograph devoted to extremely relevant, but very difficult question — to extremism. Authors make a start from the fact that the problem of fight against extremism is insufficiently studied in the Russian and foreign social and political sciences, and make a significant contribution to the solution of this problem. The appeal to extremism in the Russian Federation should be considered understandable. This phenomenon is recognized as one of the most serious threats of national security of our country.